Zeeman splitting via spin-valley-layer coupling in bilayer MoTe2. Issue 1 (December 2017) - Jiang, Chongyun; Liu, Fucai; Cuadra, Jorge; Huang, Zumeng; Li, Ke; Rasmita, Abdullah; Srivastava, Ajit; Liu, Zheng; Gao, Wei-Bo
Abstract Atomically thin monolayer transition metal dichalcogenides possess coupling of spin and valley degrees of freedom. The chirality is locked to identical valleys as a consequence of spin–orbit coupling and inversion symmetry breaking, leading to a valley analog of the Zeeman effect in presence of an out-of-plane magnetic field. Owing to the inversion symmetry in bilayers, the photoluminescence helicity should no longer be locked to the valleys. Here we show that the Zeeman splitting, however, persists in 2H-MoTe2 bilayers, as a result of an additional degree of freedom, namely the layer pseudospin, and spin–valley-layer locking. Unlike monolayers, the Zeeman splitting in bilayers occurs without lifting valley degeneracy. The degree of circularly polarized photoluminescence is tuned with magnetic field from −37% to 37%. Our results demonstrate the control of degree of freedom in bilayer with magnetic field, which makes bilayer a promising platform for spin-valley quantum gates based on magnetoelectric effects. Monolayer transition metal dichalcogenides host a valley splitting in magnetic field analogous to the Zeeman effect. Here, the authors report that the Zeeman splitting still persists in bilayers of MoTe2 without lifting the valley degeneracy, due to spin–valley-layer coupling.